Louis L'Amour western collection - Elliott, Sam, 1944-; Selleck, Tom, 1945-; Osterhage, Jeff.; Ross, Katharine, 1942-; L'Amour, Louis, 1908-1988. (Burbank, CA : Warner Home Video, 2010)
The story of the three Sackett brothers, Tye, Orrin, and Tell, who leave Tennessee to start new lives in the West; not being a man to settle down, cowhand Conn Conagher drifts in and out of widow Evie Teale's life; career outlaw Catlow attempts to take some Confederate gold, with his friend, a U.S. marshal, and a ruthless bounty hunter on his tail.
The Sacketts (1979) / produced by Jim Byrnes, Douglas Netter ; written by Jim Byrnes ; directed by Robert Totten -- Conagher (1991) / produced by Sam Elliott, John A. Kuri ; teleplay by Jeffrey M. Meyer, Sam Elliott, Katharine Ross ; directed by Reynaldo Villalobos -- Catlow (1971) / produced by Euan Lloyd ; screenplay by Scott Finch, J.J. Griffith ; directed by Sam Wanamaker.
Based on novels by Louis L'Amour.
Sam Elliott, Tom Selleck, Katharine Ross, Yul Brynner, Richard Crenna.
MPAA rating: Not rated.
DVD.
In English variously with optional English, French or Spanish subtitles.
Keywords: L'Amour, Louis, -- 1908-1988 -- Television adaptations; L'Amour, Louis, -- 1908-1988 -- Film adaptations; Frontier and pioneer life -- West (U.S.) -- Drama; Brothers -- Drama; Cowboys -- Drama; Outlaws -- Drama; West (U.S.) -- Drama; Western television programs; Television adaptations; Western films; Film adaptations; DVD; Films for the hearing impaired